Characterization and chemical modification of PLN-1, an exopolysaccharide from Phomopsis liquidambari NJUSTb1. (1st February 2021) - Liu, Jun-Sheng; Zeng, Yue-Xiang; Bi, Shi-Yuan; Zhou, Jin-Wei; Cheng, Rui; Li, Jing; Jia, Ai-Qun
Graphical abstract: Highlights: Exopolysaccharide PLN-1 was characterized by chromatography and spectral methods. PLN-1 consisted of glucose with traces of mannose and galactose and a Mw of 343 kDa. DSs of the sulfated and carboxymethylated PLN-1 were 1.228 and 0.903, respectively. Sulfated PLN-1 presented stronger moisture absorption and retention properties. Abstract: Phomopsis liquidambari is a classical endophytic fungus with great application potential in ecology and agriculture; however, studies on its exopolysaccharides are lacking. Here, we aimed to evaluate the structure and bioactivity of PLN-1, an exopolysaccharide derived from the P. liquidambari NJUSTb1 strain. The structure was elucidated by chromatography/spectral methods and hydrolyzation. Immunomodulation, moisture absorption, and retention properties were investigated after sulfation and carboxymethylation modification. Results showed that PLN-1 contained a linear repeating unit of →[4)- α -d -Glc p -(1→6)- α -d -Glc p -(1→4)- α -d -Glc p -(1→4)- α -d -Glc p -(1→]n, with a molecular weight of 343 kDa. The degrees of substitution of sulfated polysaccharide (S-PLN-1) and carboxymethylated polysaccharide (C-PLN-1) were 1.228 and 0.903, respectively. S-PLN-1 showed stronger moisture absorption and retention properties than PLN (crude EPS), C-PLN1, and PLN-1. Furthermore, PLN, S-PLN-1, and C-PLN-1 stimulated the proliferation of RAW 264.7 cells with no cytotoxicity. The elucidation of PLN-1 in this study paves the way for future applications.